Manipueira e hidrolisado da casca de Mandioca (Manihot esculenta Crantz). - Torres, Daiana Rodrigues (2014)
The interest in obtaining food of high commercial value and low cost has led researchers to seek new food sources capable of satisfying the nutritional needs. And for this purpose, have been studied for decades, the production of Single Cell Protein (SCP). Among the advantages presented in the production of SCP, the versatility of substrates used in the preparation of the microbial biomass has drawn attention. Thus, agroindustrial waste, low cost substrates and nutritionally rich for the growth of microorganisms appear as a way to reduce the production costs of the SCP. Since the local availability of waste from the processing of cassava in the region, this study aimed to investigate the biomass of Amazonian yeasts (single cell protein) using cassava and hemicellulosic hydrolyzate of cassava peel in submerged bioprocess. In this work 20 yeast to environmental, non- toxigenic, belonging to the collection of microorganisms of INPA were investigated. These were subjected to submerged bioprocess using cassava and hemicellulosic hydrolyzate as the substrate, the end of the process was measured to produce cell biomass, microorganism and the appropriate substrate were investigated by means of kinetic study. The kinetic study was performed with the whole yeast/substrate apresentarou the best growth characteristics in screening assays. Assays were performed in periods of 24h to 120h (24h, 48h, 72h, 96h and 120h) to assess the ideal for higher biomass production time. At the end of each trial were analyzed characteristic pH, Brix, glucose, optical density and dry biomass to identify the best process time. Finally, the biomass obtained was quantified for the levels of total protein. It was also tealizado from an experimental design, optimization of the process for obtaining the hydrolyzate evaluate the influence of hydrolysis time and the concentration of sulfuric acid (H2SO4) is necessary to obtain a hydrolyzate with higher concentrations of sugars. The experimental design used was more like 22 axial points. The microorganism used for evaluation of biomass production was the yeast Rhodotorula sp. (LMM 4375), belonging to the collection of microbiological cultures INPA. The selected yeast underwent bioprocess, for 96 hours, 100 rpm, with cell concentration 1x104cel/mL, being measured at the beginning and end of each procedure the ºBrix of the substrate and the end of the bioprocess biomass obtained was quantified. In screening tests, the isolated Rhodotorula LMM 4375, showed the highest cell concentration (9.64x107  1.58x107) when using the hydrolyzate of cassava peel as substrate. Kinetic study of the selected strain, isolated Rhodotorula LMM 4375 presented the highest yield and conversion of nutrient/biomass between 48-96 h. When evaluated on the content of this biomass obtained proteins, isolated Rhodotorula LMM 4375 presented content equal to 23 % of protetínas. The factorial design allowed analysis of the response surface showing the optimal concentrations for maximum production of the hydrolyzate Brix: Time hydrolysis ratio of 9.5 minutes and 0.2 g H2SO4/g of cassava peel and biomass production: Time hydrolysis ratio of 19.5 minutes and 0.14 gH2SO4/g of cassava peel. Thus, one can observe the potential use of the peel the cassava hydrolyzate as a substrate for the production of yeast biomass and also the LMM protencial strain 4375, as a source of single cell protein. Keywords: Single cell protein, yeast, agroinduztriais waste.